PS39 Alcohol and Harm to Others in Russia: Longitudinal Analysis of Couple Drinking and Subsequent Divorce. (17th September 2012) - Keenan, K; Grundy, E; Kenward, MG; Leon, DA
Abstract : Background: In Russia male drinking patterns have serious negative health effects; however the impact of alcohol on divorce is relatively unexplored. In other settings heavy drinking and discrepant drinking within couples increases the probability of marital breakdown. Longitudinal data, rather than cross-sectional, is preferable to establish the direction of any causal link. Methods: The association between married couple drinking patterns and subsequent divorce was investigated in a national population-based panel study in Russia. Follow-up data on 4, 266 married couples was extracted from 14 consecutive annual rounds (1994–2009) of the Russian Longitudinal Monitoring Survey. The overall follow-up rate of couples was 90%, and loss to follow-up was unrelated to drinking behaviour. At interview couples provided information about family relationships, drinking habits in the last 30 days and socio-demographic variables. Discrete time hazard models were fitted using pooled logistic regression to estimate the probability of divorce among married couples as a function of the previous round's drinking patterns and other covariates. Results: Increased odds of divorce were associated with greater frequency of husband drinking (P<0.001) and greater frequency of wife drinking (P<0.001), and remained significant after mutual adjustment. Wife's hazardous drinking was also associated with a higher risk of divorce (OR 1.45, 95% CI 1.06–1.92) after adjustment for husband's drinking. Husbands who were abstainers also had raised odds of divorce compared to moderate drinkers (OR 1.36, CI 1.01–1.84). There was a significant positive relationship between husband's maximum daily volume of ethanol from vodka and divorce, after adjustment for frequency. After testing for interaction between husband's and wife's drinking, there was no evidence that couples with discrepant drinking frequencies had increased risk of divorce. Conclusion: This study adds to the very sparse literature investigating the association of drinking with divorce using longitudinal data. The results suggest that in Russia heavy and frequent drinking of both husbands and wives put couples at greater risk of future divorce. The thresholds where frequency and volume adversely affect marital stability are higher in husbands, than in wives. Male abstainers have a higher degree of marital dysfunction, lending support to the idea that many Russian male abstainers are ex-drinkers. More research is needed to understand the causal pathways from drinking to marital breakdown in Russia, and the overall population-level impact of drinking on partnerships.